Caracterização e zoneamento ambiental do zoológico municipal de Mogi Mirim-SP - Marino, Luciana Mara Ribeiro (Universidade Federal de São Carlos, 2008)
The modern Zoos are in a continuous improvement for the attendance of your principal functions - leisure, education, conservation and research. The understanding of the relationship among the environmental protection (preservation, conservation and recovery) and the public use of the Zoos for activities recreational or educational has been the administrators' of these institutions great challenge. The present work had as objective the environmental characterization and zoning of the Municipal Zoological Park of Moji Mirim and its immediate surrounding to subsidize your management plan. The Zoological Park environmental characterization was made based on the use of Geographical Information Systems, making possible the elaboration of a georeferenced database and thematic maps of several landscape structural elements (limits, hydrography, road net and land use). These results allowed the proposition of a Zoo s conceptual environmental zoning and for your buffer zone, in terms of the environmental risks resulting from the types and intensities of the immediate surrounding land uses. The environmental zoning constitutes the primary component of a management plan, a public declaration document of the institution manager's of the Zoological Park intentions in the perspective to assure the execution of your functions
Keywords: Zoneamento ambiental; Zoneamento; Planejamento ambiental; Zoológico; CIENCIAS BIOLOGICAS::ECOLOGIA